Risk Factors for Postoperative Urinary Tract Infections in Patients Undergoing Total Joint Arthroplasty. (28th November 2016) - Alvarez, Andrew P.; Demzik, Alysen L.; Alvi, Hasham M.; Hardt, Kevin D.; Manning, David W.
Abstract : Background . Urinary tract infections (UTIs) are the most common minor complication following total joint arthroplasty (TJA) with incidence as high as 3.26%. Bladder catheterization is routinely used during TJA and the Centers for Medicare and Medicaid Services (CMS) has recently identified hospital-acquired catheter associated UTI as a target for quality improvement. This investigation seeks to identify specific risk factors for UTI in TJA patients. Methods. We retrospectively studied patients undergoing TJA for osteoarthritis between 2006 and 2013 in the American College of Surgeon's National Surgical Improvement Program Database (ACS-NSQIP). A univariate analysis screen followed by multivariate logistic regression identified specific patient demographics, comorbidities, preoperative laboratory values, and operative characteristics independently associated with postoperative UTI. Results. 1, 239 (1.1%) of 115, 630 TJA patients we identified experienced a postoperative UTI. The following characteristics are independently associated with postoperative UTI: female sex (OR 2.1, 95% CI 1.6–2.7), chronic steroid use (OR 2.0, 95% CI 1.2–3.2), ages 60–69 (OR 1.5, 95% CI 1.0–2.1), 70–79 (OR 2.0, 95% CI 1.4–2.9), and ≥80 (OR 2.3, 95% CI 1.5–3.6), ASA Classes 3–5 (OR 1.5, 95% CI 1.2–1.9), preoperative creatinine >1.35 (OR 1.8, 95% CI 1.3–2.6), and operation time greater than 130 minutes (OR 1.8, 95% CI 1.3–2.4). Conclusions. In this large database query, postoperative UTI occurs in 1.1% of patients following TJA and several variables including female sex, age greater than 60, and chronic steroid use are independent risk factors for occurrence. Practitioners should be aware of populations at greater risk to support efforts to comply with CMS initiated quality improvement.